The Effect of Audio-Visual Learning Media on Language Skills in Children Aged 4-5 Years - Intisari; Rahmat, M. Yusran; Hasbur, Heni Safitri; Fatimah, Husnul (Al-Mudarris, 2025)
Language is the main foundation of early childhood development that affects thinking skills, social interaction, and character formation and moral awareness. From the perspective of Islamic pedagogy, language is not only a means of communication, but also a divine mandate (amanah al-lughah) or a means to express gratitude and cultivate manners in speaking. This study aims to determine the influence of audio-visual learning media on the language skills of children aged 4-5 years in Anggrek 2 Kindergarten, Gantarang District, Bulukumba Regency. The approach used was a pre-experimental design of the One Group Pretest–Posttest Design. A total of 12 children were purposively selected as samples, and data were analyzed using the Wilcoxon Signed Rank test. The results of the study showed a significant increase in receptive and expressive language skills after the application of audio-visual learning media. These findings confirm that audio-visual media not only strengthens children's linguistic skills through engaging and interactive learning experiences, but also has the potential to foster the values of empathy, good manners, and spiritual awareness through educational and moral content. Thus, audio-visual media can be a learning strategy that is not only academically effective, but also humanistically and religiously meaningful to support early childhood development holistically.